Peran Ustazah dalam Mengembangkan Coping Stres pada Santri Tahfiz Dayah Ummul Qura Kecamatan Tanah Jambo Aye - Mahera, Ulfa; Zain, Arifin; Jarnawi, Jarnawi (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2026)
Students of the Islamic memorization program at Ummul Qura Islamic boarding school experience various academic pressures that can lead to stress. This pressure arises when students experience difficulty memorizing, are unable to achieve memorization targets, and face dense learning activities in the Islamic boarding school environment. This condition requires students to have good stress coping skills in order to be able to manage the pressure experienced adaptively. In this context, the role of ustazah as educators and mentors is very important in helping students develop stress coping skills during the process of memorizing the Qur'an. This study aims to determine the forms of stress experienced by Islamic memorization students, the stress coping strategies used, and the role of ustazah in developing stress coping for students at Ummul Qura Islamic boarding school, Tanah Jambo Aye District, North Aceh Regency. The scope of the study focuses on the experiences of stress among Islamic memorization students and the role of ustazah in providing guidance, mentoring, and emotional and spiritual support. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of 2 ustazah and 6 Islamic memorization students selected through a purposive sampling technique. Data collection was conducted through observation, semi-structured interviews, and documentation. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that students experience stress in the form of academic, emotional, physical, and behavioral pressure. To overcome this stress, students use problem-focused coping, emotion-focused coping, and spiritual coping strategies. In addition, the female teacher acts as a guide, motivator, and role model through a personal approach, emotional support, and reinforcement of spiritual values that help students manage stress and maintain emotional balance during the process of memorizing the Quran.